PSI Mehler reaction is the main alternative photosynthetic electron pathway in Symbiodinium sp., symbiotic dinoflagellates of cnidarians. Issue 1 (30th June 2014) - Roberty, Stéphane; Bailleul, Benjamin; Berne, Nicolas; Franck, Fabrice; Cardol, Pierre
Summary: Photosynthetic organisms have developed various photoprotective mechanisms to cope with exposure to high light intensities. In photosynthetic dinoflagellates that live in symbiosis with cnidarians, the nature and relative amplitude of these regulatory mechanisms are a matter of debate. In our study, the amplitude of photosynthetic alternative electron flows (AEF) to oxygen (chlororespiration, Mehler reaction), the mitochondrial respiration and the Photosystem I (PSI) cyclic electron flow were investigated in strains belonging to three clades (A1, B1 and F1) of Symbiodinium . Cultured S ymbiodinium strains were maintained under identical environmental conditions, and measurements of oxygen evolution, fluorescence emission and absorption changes at specific wavelengths were used to evaluate PSI and PSII electron transfer rates (ETR). A light‐ and O2 ‐dependent ETR was observed in all strains. This electron transfer chain involves PSII and PSI and is insensitive to inhibitors of mitochondrial activity and carbon fixation. We demonstrate that in all strains, the Mehler reaction responsible for photoreduction of oxygen by the PSI under high light, is the main AEF at the onset and at the steady state of photosynthesis. This sustained photosynthetic AEF under high light intensities acts as a photoprotective mechanism and leads to an increase of the ATP/NADPH ratio.